THE EFFECT OF GREEN ACCOUNTING, ASSETS TURNOVER, ECO-EFFICIENCY, AND FINANCIAL CONSTRAINTS ON FIRM VALUE - Dian Saputra; Zidan Dwinanda Arifin (International Conference On Law And Social Sciences, 2024)
This study analyses the effect of green accounting, assets turnover, eco-efficiency, and financial constraints on firm value in the energy sector on the Indonesia Stock Exchange for the period 2020- 2022. Financial statement data from 52 energy sector companies were used for analysis with multiple regression using SmartPLS 3. The results show that green accounting, assets turnover, and eco- efficiency have a significant effect on firm value, while financial constraints have no significant effect. The implications of this study provide important insights into the factors that influence firm performance and value in the energy sector, as well as the importance of green accounting, assets turnover, and eco- efficiency practices in increasing firm value. This research is expected to contribute to practitioners, regulators, and stakeholders of the Indonesian energy sector in understanding the influence of these factors.